Derived CDG for bioassay – a tool for screening people in a radiological emergency (Brazilian Journal of Radiation Sciences (BJRS), 2021)
The decision on initiating clinical treatment for a person who has been internally contaminated by radionuclides is not trivial. NCRP Publication 161 presented an operational quantity named Clinical Decision Guide - CDG to help in this decision. The bases for establishing the CDG values are dose values related to the risks of stochastic and deterministic effects to body tissues. This work shows a computational system -  Derived CDG -  which calculates CDG and derived CDG applied to in vivo and in vitro radiobioassay for several age groups and for several times after intake by inhalation and ingestion. It is a tool to be used to screen people with internal contamination who need medical follow-up. The system enables the users to change parameters used in calculation for different simulated scenarios.